1996
DOI: 10.1177/156482659601700211
|View full text |Cite
|
Sign up to set email alerts
|

Development of Weaning Foods Based on Malted, Popped, and Roller-Dried Barley and Chickpea

Abstract: The optimum conditions for malting barley and chickpea were standardized, and a malted weaning food (MWF) formulation was prepared by blending 48-hour germinated barley and 24-hour germinated chickpea flours. Decorticated barley was mixed with 7% additional water, tempered for four hours, and popped in hot sand medium. Popped barley was mixed with popped chickpea to formulate popped weaning food (PWF). Flours from decorticated and mild toasted barley and chickpea were mixed with water and the slurry was roller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 11 publications
5
20
0
Order By: Relevance
“…The PER values of these malt-based foods are comparable with the earlier reports on PER values of foods based on malted cereals, legumes, and milk Livingstone et al, 1993;Wondimu and Malleshi, 1996;Sumathi, 1997). However, NPR values for the enteral food formulae were lower than the PEF (Table 5.3 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The PER values of these malt-based foods are comparable with the earlier reports on PER values of foods based on malted cereals, legumes, and milk Livingstone et al, 1993;Wondimu and Malleshi, 1996;Sumathi, 1997). However, NPR values for the enteral food formulae were lower than the PEF (Table 5.3 ).…”
Section: Resultssupporting
confidence: 89%
“…A biscuit formulation based on malted wheat and legumes was found to be a suitable nutrition supplement for the aged (Sumathi, 1997). Malted cereal flours, which are also known as amylase-rich food (ARF), are effectively used to reduce the viscosity of cereal-legume-based weaning foods (Mosha and Svanberg, 1983;Malleshi and Desikachar, 1988;Almeida-Dominguez et al, 1993;Wondimu and Malleshi, 1996). Beverages based on cereal malt and milk have also been prepared (Javalagi and Vaidehi, 1986;Singh and Bains, 1988).…”
Section: Nutritious Foods Based On Malted Cereals and Legumesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of cereal/legume complementation has been applied to improve protein quality. Researchers have shown that legume proteins (rich in lysine) and cereals (low in lysine) mixed in the right proportion could provide a balanced mixture of amino acids (Wondimu and Malleshi 1996).…”
mentioning
confidence: 99%
“…There are many sources of protein available to children. FAO/WHO has adopted a proteincorrected amino acid, as the preferred method of measuring the value of protein in human nutrition (Hulse 1989;Wondimu and Malleshi 1996).…”
Section: Anti-nutritional Factormentioning
confidence: 99%